Computing the pressure of agricultural tractors on soil and mapping its compaction - I. P. Adylin; A. Comparetti; C. Greco; V. P. Lapik; P. V. Lapik; S. Orlando (Бюллетень Почвенного института им. В.В. Докучаева, 2024)
Manufacturers of agricultural machines, when designing, pay a little attention to its impact on soil, thus producing models with high compression loads on the soil or with a small contact area between the tyres/tracks and the soil surface. Therefore, the aim of this study is to evaluate the negative impact of both wheeled and tracked agricultural tractors on the soil, in terms of soil compaction, and its causes (i. e. design features of tractor tyres/tracks), during the last six decades (i. e. from 1961 to 2021). Soil compaction is caused by the pressure applied by agricultural machines on the soil through the contact area of their tyres/tracks with the soil surface. So, the main indicator of the negative impact on the soil by the tractors manufactured during the last 60 years, i. e. the average pressure applied by the tyres or tracks of tractors manufactured in EU and in the post-Soviet cuntries from 1961 to 2021 to the soil, was computed. A general decrease of the average pressure of the tyres/tracks on the soil can be observed in 1980s and 1990s, followed by its general increase since 2000, above all for the tractors having power higher than 140 kW. Thus, there is an urgent need to assess spatial and temporal changes in soil vulnerability to compaction, that depends on weather conditions and soil properties, as well as agricultural management practices, and can only be fully assessed by means of a combination of traditional techniques (i. e. use of soil cone penetrometer followed by 2D mapping using GIS or 3D mapping through geostatistics) and mechanical approaches (i. e. computation of agricultural machine parameters – soil contact area). The results show that tractor manufacturers did not take care of reducing soil compaction during the considered period.